PENATAAN RUANG KOTA DALAM PERSPEKTIF SOSIAL, EKONOMI DAN SUMBER DAYA ALAM - SOEPARDI HARRIS (Sosio e-Kons, 2015)
The city is one of the places with the complexity of human life is very high. The city is also the meeting place of humans with various interests in a large hall the city is an organism grows a variety of activities such as the center of government, industry, economy,and education. With a very high heterogeneity, such as arranging the city will organize the tangled threads. Various theories and approaches applied in order to get the right solution, one of which is the approach to social, economic and natural resources. Keywords: arrangement, space, city.